PLAYFUL IN PRAYER AND SERIOUS IN SEX: MODERNIST AND POSTMODERNIST TENDENCIES IN JOB’S HALLELUJAH - Moyo, Gankhanani Moffat (European Scientific Journal, ESJ, 2014)
This paper follows the poetry of Zambian singer JOB. It explores the modernist and postmodernist elements in the work. The work opens with an examination of the statement “Forgive me father for I have sinned” and how JOB has used it in his poem. The work further studies modernist and postmodernist literary elements before considering how they have been used in JOB’s ‘Hallelujah’. It is learnt that the elements in JOB’s poem include deception, failed technology, and pastiche. The paper finally concludes that the poets presentation of his work in this manner is in relation with his desire to be different from the other singers of his age.